KONVERGENSI TANGGUNG JAWAB PIDANA DAN PERDATA DALAM TINDAK PIDANA KERUGIAN NEGARA: KAJIAN PUSTAKA ATAS DUALITAS SANKSI DAN RESTITUSI - Gunawan Widjaja (INTELIGENSIA MEDIA, 2026)
This article aims to analyse the convergence of criminal and civil liability in criminal offences causing loss to the state through a literature review of the duality of sanctions and restitution. This issue is significant because loss to the state resulting from criminal offences, particularly corruption, requires not only the punishment of the perpetrators but also the tangible recovery of state funds through effective legal mechanisms. The findings indicate that the duality of criminal and civil sanctions constitutes a form of convergence of legal instruments, wherein criminal law serves to establish guilt and impose sanctions, whilst civil law serves to recover state losses through claims for damages, asset recovery, and restitution mechanisms. This study also found that restitution in cases of state losses cannot be narrowly interpreted as mere payment of damages, but rather as part of an asset recovery strategy that links the functions of punishment, recovery, and protection of the public interest. However, the effectiveness of this convergence still faces obstacles in the form of regulatory disharmony, limitations in asset tracing, and weak coordination between law enforcement agencies, meaning that the objective of recovering state losses has not always been optimally achieved. Therefore, there is a need to strengthen harmonisation between the criminal and civil regimes, optimise restitution mechanisms, and reformulate asset recovery policies so that law enforcement against criminal acts causing state losses can achieve justice, legal certainty, and public benefit in a balanced manner.